COMMUNICATION SKILLS IN A FOREIGN LANGUAGE - Imangali Shugyla Abdykarymkyzy; Abdikamal Karina; Erbolkyzy Asemai (Research Retrieval and Academic Letters, 2023)
The formation of professional and methodological training of students in the process of teaching English language areas also requires a focus on the issue of language development. A student who is able to correctly recognize and analyze the grammatical nature of words, models of word personalities, that is, correctly use the knowledge gained in practice, will be able to clearly and clearly express his thoughts to the listener. This is done by the fact that the student learns the complex morphological structure of the English language on the basis of language development work. Therefore, there is a need for scientific and methodological study of the development of the student's language through training in the field of modern English morphology as the main condition for identifying with today's socio-social demand. The development of the student's language is carried out productively through linguistic participatory activity, because "language communication means understanding through spoken language, which has more roots than just communication, has its own place in life, the exchange of views of people with each other through a set of socio-social information necessary for the development of society, is the root of human relations. "The goal of language development is to ensure free communication in society through the English language. Therefore, in teaching language as a means of communication, teaching grammar serves as a mechanism for implementing communication. Thus, the ability of a student to effectively and reasonably use the knowledge gained in the field of Science in language communication is an urgent problem arising from the demand of the present time.